Multiscale Approach to the Study of the Electronic Properties of Two Thiophene Curcuminoid Molecules. Issue 36 (26th July 2016) - Etcheverry‐Berríos, Alvaro; Olavarría, Ignacio; Perrin, Mickael L.; Díaz‐Torres, Raúl; Jullian, Domingo; Ponce, Ingrid; Zagal, José H.; Pavez, Jorge; Vásquez, Sergio O.; van der Zant, Herre S. J.; Dulić, Diana; Aliaga‐Alcalde, Núria; et al.
Abstract: We studied the electronic and conductance properties of two thiophene–curcuminoid molecules, 2‐thphCCM (1 ) and 3‐thphCCM (2 ), in which the only structural difference is the position of the sulfur atoms in the thiophene terminal groups. We used electrochemical techniques as well as UV/Vis absorption studies to obtain the values of the HOMO–LUMO band gap energies, showing that molecule1 has lower values than2 . Theoretical calculations show the same trend. Self‐assembled monolayers (SAMs) of these molecules were studied by using electrochemistry, showing that the interaction with gold reduces drastically the HOMO–LUMO gap in both molecules to almost the same value. Single‐molecule conductance measurements show that molecule2 has two different conductance values, whereas molecule1 exhibits only one. Based on theoretical calculations, we conclude that the lowest conductance value, similar in both molecules, corresponds to a van der Waals interaction between the thiophene ring and the electrodes. The one order of magnitude higher conductance value for molecule2 corresponds to a coordinate (dative covalent) interaction between the sulfur atoms and the gold electrodes. Abstract : In pole position : Different sulfur atom positions in the terminal thiophene rings of two curcuminoid molecules and their anchoring between two gold electrodes influence the conductance values measured by using mechanically controlled break junction (MCBJ) methods (see figure).